Subclinical Left Ventricular Disfunction in Obese Children: Are we Late? - Riaño-Mendez, B; Campo, M Ruiz-del; Garcia-Navas, P; Ibiricu-Lecumberri, A; Prado, MY Ruiz-del (Cardiology and Cardiovascular Medicine, 2023)
Aim: Longitudinal global strain (LGS) is reduced in obese patients with preserved ejection fraction of the left ventricle (LV). TAPSE/PAPS ratio, recently described, may be a step forward a more efficient RV function evaluation. The aim of the present study was to screen left and right subclinical dysfunction in obese pediatric patients without comorbidities. Methods: This case-control study compared 104 children aged 5-18 years between October 2017 and February 2019, 52 obese children with body mass index (BMI) > mean +2SD, and 52 matched controls. They were screened for other cardiovascular risk factors like insulin resistance or hypercholesterolemia. A complete echocardiography including standard and functional parameters was performed. Results: Obese children presented worse longitudinal LV function (LGS -15,90% ± 3,84 SD) in comparison with non-obese children (-19,44% ± 5,75, p=0,001). LGS correlated positively with BMI. Standard echocardiography also revealed LV dilatation and hypertrophy. TAPSE/ PAPS ratio correlated negatively with total cholesterol (r -0,419, p=0,006) and triglycerides levels (r -0,503, p=0,002). HOMA-IR (r -0,458, p=0,006) correlated negatively with E/A ratio of left ventricle. Conclusion: Remodeling of LV and sub clinic systolic dysfunction could be relatively common in asymptomatic patients with obesity and easily detected by functional echocardiography. It is necessary to perform a standardized cardiovascular evaluation in obese children for early identification of subclinical dysfunction especially in those with insulin resistance and dyslipidemia.